SOSIALISASI KEWIRAUSAHAAN DI KAMPUNG NEGARA HARJA - Julian, Nabila Arnelis; Ratu Ardila, Chytya Ike; Hartofa, Wafieq Bidzikrul; Maulana, Jogi Putra; Pakpahan, Rizqi Bonar Syahputra; Prameswari, Adelia Putri; Syaffanaztiti, Meza Difia (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2024)
This research details the socialization and implementation strategies of the entrepreneurship program, with a focus on increasing interest, in each community circle in Kampung Negara Harja. The main objective of this research is to increase the understanding, skills, and active participation of the Kampung Negara Harja community in building interest in entrepreneurship. The research method involved a series of activities, including socialization workshops, mentoring sessions, and monitoring during the research period. Socialization was conducted to provide an in-depth understanding of the benefits of entrepreneurship, while training focused on developing entrepreneurial interest. This article is limited to the implementation of KKN University of Lampung Period 1 2024